Electronic gadgets for the evil genius - Iannini, Robert E. (Evil genius series., 2014)
Spark your creativity with this wickedly inventive guide. Electronic Gadgets for the Evil Genius, Second Edition, is filled with completely new, amped-up projects that will shock and amaze, such as super-big Tesla coils, lasers, plasma devices, and electrokinetics contraptions. Using affordable, easy-to-find components and equipment, each do-it-yourself project begins with information on safety, the difficulty level, practical uses for the gadget, and the tools needed to complete the project. You'll gain valuable skills while enjoying hours of rewarding--and slightly twisted--fun!